Mycological and cytological examination of oral candidal carriage in diabetic patients and non-diabetic control subjects: thorough analysis of local aetiologic and systemic factors - AKYÜZ, SERAP HATİCE (BLACKWELL PUBLISHING LTD, 2002)
In this study, 55 diabetic patients and 45 non-diabetic control subjects were examined to determine oral candidal carriage state. The influence of some local aetiologic and systemic factors such as: salivary flow rate and pH, heredity, alcohol drinking, smoking habits, antimicrobial therapy, wearing of denture, burning sensation, dry mouth, taste alteration and tooth brushing habit on candidal carriage rate were investigated. Imprint culture, cytological smears and biochemical tests were used. Oral carrier rate and density of Candida species were non-significantly higher in the diabetic patients than in the non-diabetic control subjects. This increase was confirmed cytologically too. In both groups, Candida albicans was found to be a predominant species on tongue dorsum. Cigarette and alcohol habits of men were higher while tooth brushing habit was less than in women in diabetic and control groups. Salivary flow rate and pH values of diabetic patients were significantly lower while serum glucose values were significantly higher than of non-diabetic controls. The rate of diabetic patients suffering from dry mouth and having diabetic heredity in the family were significantly higher than control subjects. The candidal colonization was higher and keratinization was lower while diabetic treatment tended from diet and oral antidiabetic towards insulin. The decrease in salivary pH, the increase in serum glucose and wearing denture were correlated with the increased rate and density of C. albicans in both groups. Keratinization was also accompanied with the increase in leucocytes. In diabetic group, positive correlations were found between antimicrobial therapy and C. glabrata carriage; the increase in leucocytes and C. albicans carriage; the increase in keratinization and alcohol habit; serum glucose and smoking habit; dry mouth complaint and antimicrobial therapy. There was a negative correlation between salivary flow rate and C. albicans carriage. In control group a positive correlation was found between antimicrobial therapy and keratinization.
Keywords: candida; diabetes; local aetiologic and systemic factors; DENTURE STOMATITIS; CIGARETTE-SMOKING; MELLITUS; PREVALENCE; ALBICANS; DISEASE